Funeral games in honor of Arthur Vincent Lourié - Móricz, Klára 1962-; Morrison, Simon Alexander 1964- (Oxford University Press, 2014)
This title explores the varied aesthetic impulses and ever-evolving personal motivations of Russian composer Arthur Lourié. A St Petersburg native allied with the Futurist movement and profoundly sympathetic to Silver Age decadence, Lourié was swept away by the Revolution; he surfaced as a Communist commissar of music before landing in Europe and America, where his career foundered. Making his way by serving others, he became Stravinsky's right-hand man.
Keywords: Lourié, Arthur, -- 1892-1966; Koussevitzky, Serge, -- 1874-1951; Lourié, Arthur Vincent -- 1891-1966; Geschichte 1891-1966; Composers -- Soviet Union -- Biography; Russischer Einwanderer; Komponist; Sowjetunion; USA; Aufsatzsammlung; Biografie; Festschrift